Same-Admission Microvascular Maxillofacial Ballistic Trauma Reconstruction Using Virtual Surgical Planning: A Case Series and Systematic Review. Issue 3 (September 2022) - Knudson, Sean A.; Day, Kristopher M.; Kelley, Patrick; Padilla, Pablo; Collier, Ian X.; Henry, Steven; Harshbarger, Raymond; Combs, Patrick
Study Design: Retrospective case series; systematic review. Objective: It is unknown whether the use of virtual surgical planning (VSP) to facilitate same-admission microsurgical reconstruction of the mandible following acute maxillofacial ballistic trauma (MBT) is sufficient to achieve definitive reconstruction and functional occlusion. Methods: A single-center retrospective analysis was conducted for patients who underwent microsurgical reconstruction of the mandible using VSP after acute MBT. The PubMed/MEDLINE, Embase, ScienceDirect, and Scopus databases were systematically reviewed using blinded screening. Studies were evaluated via thematic analysis. Results: Five patients were treated by same-admission and microsurgical reconstruction of the mandible using VSP. We observed an average of 16.4 ± 9.1 days between initial presentation and reconstruction, an average length of stay of 51.6 ± 17.9 days, 6.2 ± 2.8 operations, and 1.6 ± 0.9 free flaps per patient. Four types and 8 total flaps were employed, most commonly the anterior lateral thigh flap (37.5%). Care yielded complete flap survival. Each patient experienced at least 1 minor complication. All patients achieved centric occlusion, oral nutrition, and an approximation of their baseline facial aesthetic. Follow up was 191.0 ± 183.9 weeks. Systematic review produced 8 articles that adhered to inclusion criteria. Consensus themes in the literature were found for clinical goal and function of VSP when practicing MBT reconstruction, yet disagreement was found surrounding optimal treatment timeline. Conclusions: Same-admission microsurgical reconstruction after MBT is safe and effective to re-establish mandibular form and function. VSP did not delay reconstruction, given the need for preparation prior to definitive reconstruction.